Highly selective one-step hydrogenation of nitrobenzene to cyclohexylamine over the supported 10% Ni/carbon catalysts doped with 3‰ Rh. Issue 19 (5th February 2016) - Lu, Xinhuan; chen, Yang; Zhao, Zhenshuang; Deng, Hao; Zhou, Dan; Wei, Changcheng; Nie, Renfeng; Xia, Qinghua
Abstract : The catalyst 3‰ Rh–10% Ni/CSC exhibits an excellent performance to achieve 100 mol% conversion of nitrobenzene and 91.6% selectivity of fully-hydrogenated cyclohexylamine under conditions of 3.5 MPa H2 and 140 °C. Abstract : The carbon supported 10% Ni catalysts doped with 3‰ Rh have been prepared by an impregnation method. These catalysts have been used to catalyze the one-step hydrogenation of nitrobenzene to cyclohexylamine. The results show that the 3‰ Rh–10% Ni/CSC (biocarbon) catalyst exhibits an excellent performance to achieve 100 mol% conversion of nitrobenzene and 91.6% selectivity of cyclohexylamine under reaction conditions of 3.5 MPa and 140 °C. The recycling tests reveal recyclable stability of 3‰ Rh–10% Ni/CSC. This catalyst is active for the hydrogenation of a series of electron-deficient nitrobenzenes. Some factors such as the type of carriers, the content of Ni and Rh, the type of metals and additives play important roles in controlling the selective hydrogenation.